Optimasi Multi Respon pada Proses Gurdi dengan Menggunakan Metode Taguchi–Grey - Bobby O. Soepangkat; Arief Wahjudi; Yopi Y. Tanoto (Institute of Research and Community Outreach, Petra Christian University, 2014)
Holes making is among the most important operations in manufacturing, and drilling is a major and common hole-making process. In this study, drilling parameters namely cutting speed, feed and point angle as drilling parameters. Each parameter has three levels. This paper is conducted for getting the best parameter setting for minimizing thrust force, torque, surface roughness and flank wear during drilling process. Drilling tests are carried out using high speed steel (HSS). Taguchi’s L9 (33) orthogonal array is used to perform drilling of S50C steel plates. Then, combination between grey relational analysis (GRA) and Taguchi’s method is used for optimizing experiment result (multi response).Experiment result show the contribution of factors in minimizing variation of multiple response, i.e., feed (61.44%), point angle (36.62%) and cutting speed (1.22%). From an optimization result that has validated in confirmation experiment, optimal response is set at 29,94 m/min for cutting speed, 0,07 mm/rev for feed and 134º for point angle.